PEMBERIAN TRICHOKOMPOS TANDAN KOSONG KELAPA SAWIT PADA BIBIT KOPI ARABIKA (Coffea arabica L.) - Sianturi, Vera Triwan; Yetti, Husna; Puspita, Fifi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this researchis to determine the effect of several doses of Trichocompost TKKS and to obtain the best dose for the growth of coffee arabica seedlings. This research has been conducted at the experimental farm, Agriculture Faculty of Riau University. This research started from March to June 2016. The research arranged experimentally by using Completely Randomized Design (CRD) which consist of 4 treatments and 5 replications so there are 20 experimental units. Each of the experimental unit consisted of 2 seedlings, so there are 40 seedlings. The treatments were tested of Trichocompost TKKS dose22,35 g/polybag, 33,525 g/polybag, 44,70 g/polybag, and 55,875 g/polybag. The data was analyzed statistically and followed by DNMRT at 5% level. Parameters measured was height of seedlings, number of leaves, leaves area, root crown ratio, and root volume. The result showed that the aplication of Trichocompost TKKS dose of 44,7 g/polybag give the best effect on the growth of coffee arabica seedlings.Â Keywords : Coffee Arabica seedling, Trichocompost, TKKSÂ